2018
DOI: 10.1017/xps.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Are There Long-Term Effects of the Vietnam Draft on Political Attitudes or Behavior? Apparently Not

Abstract: The Vietnam draft lottery exposed millions of men to risk of induction at a time when the Vietnam War was becoming increasingly unpopular. We study the long-term effects of draft risk on political attitudes and behaviors of men who were eligible for the draft in 1969–1971. Our 2014–2016 surveys of men who were eligible for the Vietnam draft lotteries reveal no appreciable effect of draft risk across a wide range of political attitudes. These findings are bolstered by analysis of a vast voter registration datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…We found that draft-eligible birthdates did indeed appear with unusually high frequency among male employees but not among female employees. Our findings dovetail with the notion that exogenously imposed military service increases rates of entering civilian US executive branch employment, thus supporting the hypothesis that wartime mobilization has influenced the contemporary administrative state continually and, for the federal government, reconciling discrepant results in the past literature (15, 16).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…We found that draft-eligible birthdates did indeed appear with unusually high frequency among male employees but not among female employees. Our findings dovetail with the notion that exogenously imposed military service increases rates of entering civilian US executive branch employment, thus supporting the hypothesis that wartime mobilization has influenced the contemporary administrative state continually and, for the federal government, reconciling discrepant results in the past literature (15, 16).…”
Section: Resultssupporting
confidence: 85%
“…The time period of the data studied here makes them roughly comparable with those of Angrist and Chen (15) and Green et al (16), which both reported the effect of the VSSL on later-life public employment. Given that this time period extends decades beyond the VSSL, estimates from our research design inevitably reflect patterns of retirement and mortality caused by draft-eligible men’s lottery numbers.…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Likewise, the threat of recruitment to military service in the U.S. during the Vietnam war led draft-eligible men to adopt liberal and anti-war positions (Erickson and Stoker 2011). However, more recent studies suggest that these effects did not endure in the long term (Green, Davenport and Hanson 2019).…”
Section: The Effects Of War On Soldiersmentioning
confidence: 99%